Proposition Framework to Application Kaizen Cost Technique of to realization Target Pricing: Practical Study in the Al-Muthanna Cement Company (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The study the problem emerged in the inability of local companies to enter the field of active competition with other companies operating in the same economic sector due to the high cost of their products, hence, the companies that want to apply this technique can effectively compete in order to achieve those objectives.  So this study focused on the goal of reducing the cost of products by reducing the cost product to a minimum , as the study was based in its hypothesis on the ability of companies to application this technique which in turn leads to increased profits under conditions of normal working and the power available and their potential in improving the quality of its products, as well as the need for full coordination between production management and other managements and levels.      The kaizen cost technique (k.c) is consider one of modern productive systems that have entered production techniques at the end of the twentieth century , this technique is reflected on the accounting process because it is used as the main tool to reduce the costs of products with keeping the quality of the products.Depending on this system is not impossible but it may be difficult in the beginning due to not providing of availability requirements and the requirements applied.Based on which enjoys the advantages of this is important for companies has called on the need to study the possibility of its application in public companies that apply the accounting system standardized by choosing one of these companies as a sample to find a company cement AL-Muthanna.  Divided into three section to this study , reviewed the first section the theory side for the kaizen costing while the second section dealt with the practical side , the study included financial and costing statements showing the impact of this approach is compared with the traditional method and three section it is including conclusions and recommendation that is conduct this study .   The finding of this study to the possibility of application of local companies for that technique and then built on the basis of the study's recommendation that all local companies with the potential application of this technique because of its advantages and benefits of achieving the objectives of those companies to reduce the cost of their products and increase the level of performance